Playing for Change: the Crystallization of Time, Space and Ideology in a Music Video from Around the World - Eric, Dicaire (Université d'Ottawa / University of Ottawa, 2019)
Online music videos have become a space for new cultural articulations. These articulations differ from one video to the next, as each instance mobilizes a particular set of production practices aimed at a specific purpose. From a theoretical standpoint, it is therefore challenging to qualify the broad cultural significance of these media objects. This thesis proposes a potential remedy to this issue, using a theoretical framework based on the theories of articulation, encoding/decoding, and crystallization to assess the cultural significance of an ideologically driven music video produced by Playing for Change—a not-for- profit organization with a mandate of uniting the world through music. These theories reveal how a cosmopolitan ideology is crystallized into the production practices of Playing for Change’s music video “One Love”. Through this theoretical mobilization, I examine the plurality of identities distilled in the music video, since it functions as a political, economic, and ideological object. These identities are crystallized on multiple levels, leading us to question whether complex articulations of this type can ever fully be conceptualized. Ultimately, I argue that the burgeoning field of music video studies must continue exploring theoretical models in order to develop adequate tools for analyzing the various elements, including discursive constructions, which characterize these complex, yet valuable, cultural objects.
Keywords: ideology; Deleuze